Experimental investigation to study the performance of cryogenic cooling in end milling of AISI P20 steel. (2021) - Ravi, S.; Gurusamy, P.
Abstract: High temperatures generated during metal removing operations of the tough metals causes tear and wear of the tool and impairs the workpiece surface quality. Generally, coolants are applied in the cutting zone to minimize the heat produced, extended life of the tool and maximize the metal removing performance. However, cutting fluids generate problems during the working situation and too generate problems during waste discard. So, there is a necessity to find an environmental and eco-friendly substitute for minimizing the usage of these cutting fluids during machining. The current paper deals with the analysis and experimentation for cryogenic lubrication using LN2 as a coolant in the temperature on the cutting zone, cutting force, the roughness of the surface and tear and wear of the tool at end milling of AISI P20 steel with uncoated carbide tools. Wet machining, as well as dry machining tests, was also performed to comparison of the results. The results showed that a significant reduction in the temperature at the cuttingzone because of better penetration of liquid nitrogen and forming lubrication layer/ cushion in the tool-chip interface.